Green Accounting and Corporate Social Responsibility: Enhancing SDG Commitment in Indonesia’s Energy Sector - Widuri, Retnaningtyas; Veronica, Angelina; Angelica, Yohana; Sany, Sany; Darmasaputra, Alan (Accounting Department, School of Business and Management - Universitas Kristen Petra, 2025)
This study investigates the implementation of Good Governance (GA) and Corporate Social Responsibility (CSR) and their relationship with the commitment of energy sector companies to achieving the Sustainable Development Goals (SDGs). In light of the growing urgency of sustainability challenges in Indonesia—particularly the deterioration of air quality—this research explores how GA and CSR practices influence corporate dedication to the SDGs. The study examines 17 energy companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023, selected through purposive sampling. Data were analyzed using WarpPLS 7.0. The findings reveal that both the application of GA and the disclosure of CSR initiatives have a positive impact on a company's commitment to the SDGs. However, CSR does not moderate the relationship between GA and SDG implementation. This study contributes to the academic literature by offering insights into the interplay between GA, CSR, and sustainability, emphasizing the importance of aligning governance and social responsibility strategies to advance sustainable development objectives.